RETINITIS PIGMENTOSA AND ITS AYURVEDIC MANAGEMENT (International Journal of Ayurveda and Pharma Research, 2021)
Retinitis pigmentosa (RP) is a group of diseases involving progressive degeneration of photoreceptor cells of retina. Usually, it starts in mid periphery and advancing towards the macula and fovea centralis. Visual symptoms are nyctalopia (night blindness), tubular vision and reduced visual field. Symptoms of RP mostly starts on early teen age and sever visual loss occurs at ages of 40 to 50 years. RP has worldwide prevalence of 1:3000 to 1:7000 people. Males are more affected than female in ratio of 3:2. Nakulandhya and Shleshmavidagdha Drishti explained under Drishtigata Roga in Ayurvedic literature. These two are described as Sannipataja Syadhi and Kaphaj Vyadhi respectively. They have close resemblance with retinitis pigmentosa in their symptomatology. In current era treatment for RP includes Gene therapy, retinal implants, Neurotrophic factor, stem cells, retinal transplants. But these treatment options are not specific and satisfactory and expensive. All these treatments are still in their early stages of research and development. Ayurvedic Panchakarma therapies and Kriyakalpa therapies can help to regulate vitiated Doshas and provide nourishment and strength to ocular tissue. These therapies can help to maintain the existing vision of patient and reduce progression of RP.